W.C. Fields from the Ziegfeld Follies and Broadway Stage to the Screen Becoming a Character Comedian - Wertheim, Arthur Frank (Palgrave Studies in Theatre and Performance History, 2016)
XXII, 270 p. 14 illus., 1 illus. in color.